2022
DOI: 10.1111/hepr.13773
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization plus a PD‐1 inhibitor with or without lenvatinib for intermediate‐stage hepatocellular carcinoma

Abstract: Aim: Transarterial chemoembolization (TACE) combined with a PD-1 inhibitor and TACE combined with a PD-1 inhibitor and lenvatinib have recently been reported as promising treatments to improve the prognosis of hepatocellular carcinoma (HCC) patients. This study aims to compare the efficacy of these two treatments.Methods: A retrospective study was conducted, and patients were recruited from two centers in China. Progression-free survival (PFS) and overall survival (OS) were compared, and the objective respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
5
15
0
Order By: Relevance
“…Moreover, we found that combination locoregional therapy was an independent factor for both better PFS and OS. This result was consistent with the results of previous studies that found that adding locoregional therapy to a lenvatinib plus a PD-1 inhibitor or lenvatinib monotherapy therapeutic regimen could lead to a high response and long survival [9,[35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we found that combination locoregional therapy was an independent factor for both better PFS and OS. This result was consistent with the results of previous studies that found that adding locoregional therapy to a lenvatinib plus a PD-1 inhibitor or lenvatinib monotherapy therapeutic regimen could lead to a high response and long survival [9,[35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…Xiang et al. reported that the triple therapy for patients with intermediate-stage HCC had an ORR of 64.3%, median OS of 26.0 months, and median PFS of 22.5 months ( 55 ). In addition, a global randomized Phase 3 LEAP-012 Study conducted in the United States is ongoing to compare TACE with or without lenvatinib plus pembrolizumab for intermediate-stage HCC that are not amenable to curative treatment.…”
Section: Therapeutic Responses Of Lenvatinib Plus Tace With Pd-1 Inhi...mentioning
confidence: 99%
“…After PD-1 inhibitors therapy, the expression of VEGF and FGF in patients with PD was significantly higher than that of SD patients ( 30 ). Lenvatinib inhibited these angiogenic growth factors and was associated with T-cell activation, enhanced the antitumor immunity, and increased the efficacy of PD-1 inhibitors ( 54 , 55 , 74 ). Additionally, the JAK/STAT3 signaling pathway was activated by FGFR2 signals accompanied with increasing PD-L1 expression according to Li et al.…”
Section: Why the Combination Therapy Of Lenvatinib Plus Tace With Pd-...mentioning
confidence: 99%
“…Treatment options include surgical resection, image-guided ablation, liver transplantation, transarterial chemoembolization (TACE), sorafenib, and lenvatinib (2). Different treatments are indicated at particular clinical stages, and combination therapies are often used (2)(3)(4). Although multiple treatment options are available, the prognosis of unresectable HCC remains poor (5).…”
Section: Introductionmentioning
confidence: 99%